دور مخرجات التعليم الثانوي في سوق العمل بإقليم ولاية قالمة - بريمة, علي (Sciences de l'Homme et de la Société, 2013)
إن العنصر البشري و ما يمتلك من طاقات خلاقة يعتبر رأس مال فكري و عاملا لا يقل أهمية عن رأس المال المادي ، بل هو الأساس في عملية التنمية داخل الاقليم، و هو العنصر الإنتاجي الأول،  كما يعتبر من بين مخرجات المدارس الثانوية التي تمثل إحدى مؤسسات الاقليم الأكثر حركية و انتاجا في الميدان العلمي و المعرفي، حيث  يفرض عليها المحيط تشكيل برامجها على نحو يعطي مزيدا من الاهتمام بالدروس العملية و التدريبات الميدانية التي تخدم الإقليم بصفة أساسية، و عليه فإن هذا المقال يهدف للتعرف على دور مخرجات التعليم الثانوي بإقليم ولاية قالمة و ما تسعى لتحقيقه من توافق مع متطلبات سوق العمل الاقليمي . The human element and which has potential for creativity is an intellectual capital and nevertheless important as physical capital factor  mainly in the development process in the country and it is the first element of production, and  considered  as one of the outputs of the secondary schools  which  constitute  one of the most dynamic and productive institutions in science and cognitive domain, because it is forced around the programs in a way that it gives importance to practical programs and trainings ground who are mainly territory. This article therefore seeks to identify the  role  of the  secondary education outputs   in the development of the territory, and what it reach to create a consensus with  the requirements of the territorial labor market.